After Governance: A Normative Re ection on Civil Society Participation in Policy Processes - Kutay, Acar (Politik, 2015)
This paper discusses the normative implications of a political vision that aims to integrate civil society into new governance mechanisms, pragmatic governance in particular, by virtue of the funding of civil society organisations. is vision has led to a marked increase in both funding for civil society and in the assignment of governance tasks to civil society organisations that are normally performed by the public sector. However, some of the crucial aspects of these normative, ontological perspectives are either counter-factual or limited by at least two major factors: 1) the prevailing technocratic style of policy making used in pragmatic govern- ance, and 2) the proliferation of managerialism, i.e. the idea that any kind of social organisation must be administered by managers and that the public and civil society sectors should use of corporate/business sector professional management techniques and tools. Both pragmatic governance and managerialism a ect, and re-de ne, the traditional conception of civil society as autonomous, authentic, voluntary organisations that act as a check and balance on the excessive use of power by the state.